Health literacy and chronic disease prevalence: age-group differences in Zhejiang, China - Zhang, Qiuhua; Huang, Zishuo; Xu, Tingke; Chen, Chun; Xu, Yue; Yao, Dingming; Hu, Xiujing; Chen, Heni; Dong, Yin; Zhang, Xuehai; Zhang, Xiangyang (Frontiers in Public Health, 2025)
BackgroundHealth literacy (HL), a key factor in chronic disease prevention, enables individuals to better understand, manage, and respond to health risks. While HL’s influence on health outcomes is established, limited research has explored how its association with chronic disease prevalence varies across age groups, particularly between middle-aged adults and young-older adults.MethodsWe used data from the 2023 China Health Literacy Survey (CHLS) in Zhejiang, which included 37,214 individuals aged 45 and older, collected through a stratified multistage probability sampling design. Participants were categorized into two age groups: middle-aged adults (45–59 years old) and young-older adults (60–69 years old). HL levels and the presence of chronic diseases were assessed. Chi-square test and multinomial logistic regression analyses were conducted to examine age-specific associations between HL and chronic disease status: (no chronic disease, one chronic disease, two or more chronic diseases), controlling for demographic covariates.ResultsAmong 37,214 participants, 20.3% had adequate HL, with a clear inverse relationship between HL and chronic disease status. Adequate HL was associated with significantly lower odds of having a single chronic disease among middle-aged adults (OR = 0.904, 95% CI: 0.836–0.978), though no such association was observed for two or more chronic diseases (multimorbidity). Furthermore, HL showed no significant association with chronic disease status across young-older populations. Consistent with these primary findings, results from all three HL dimensions—knowledge and attitudes, behavior and lifestyle, and health-related skills—aligned with this pattern.ConclusionThe study identified age-related differences in the link between HL and chronic disease. Among middle-aged adults, adequate HL was associated with significantly lower odds of a single chronic condition though not with multimorbidity, while no significant HL-chronic disease association existed in young-older populations. These findings underscore the need for targeted HL interventions tailored to middle-aged populations to mitigate early chronic disease onset.